#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# If the sum of first p terms of an A.P. is equal to the sum of the first q terms, then find the sum of the first (p + q) terms

10 years ago

Dear Chanchal,

equate sum of first p and q terms then write d multiplied by its coefficients on one side and a and its coefficients on the other and cancel (p-q) factor, collect all terms one side and you will get expression similar to that of  p+q term's sum which will give you value of sum as 0.

Now you can win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.

10 years ago

A/Q,

p/2(2a+(p-1)d)=q/2(2a+(q-1)d)

=)p(2a+(p-1)d)=q(2a+(q-1)d)

=)2ap+p(p-1)d=2aq+q(q-1)d

=)2ap-2aq=d(q(q-1)-p(p-1))

=)2a(p-q)=d(q^2-p^2+p-q)

after solving you get,  2a=-(p+q-1)d............................(1)

NOW

sum upto (p+q) terms = (p+q)/2(2a+(p+q-1)d)

=(p+q)/2(2a-2a)                                  (from 1)

=0.

best of luck.........................

10 years ago

let the first term and common difference of AP is a and d....

sum of first q terms =sum of first p terms =k

q/2{2a+(q-1)d} = p/2{2a+(p-1)d} = k

2a = 2k(q+p-1)/pq   and d=-2k/pq

now sum of first p+q terms =Sp+q= p+q/2 {2a +(p+q-1)d}

=(p+q)/2{2k(p+q-1)/pq  - 2k(p+q-1)/pq }

=0 AKASH GOYAL AskiitiansExpert-IITD
419 Points
10 years ago

one question to all of you solved this wat will be the sum when p-q=0 that is p=q this is the difficult case. why you neglected this case.

10 years ago

The sum to n terms of an AP is given by the general expression We have Since p,q are assumed unequal, we have so that the sum of (p+q)

terms is 0